Analisis Kebutuhan E-Modul Biologi Terintgrasi Nilai Imtaq Pada Materi Sistem Pertahanan Tubuh Manusia - Dhiyah Maharani; Siti Robiah (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research aims to find out information about the needs of teachers and students in student learning on the material of the human body's defense system. This research was conducted at MAN 2 Pekanbaru using a qualitative descriptive method using a population of 35 students from class XI MAN 2 Pekanbaru and using a sample of 10 students from class XI MAN 2 Pekanbaru. The instruments used were teacher and student interviews and documentation. analyzed using descriptive statistical data analysis techniques. Descriptive statistical analysis techniques are statistics that describe or describe an object that has been examined from the sample or population data obtained. The results of this research are obtained from teacher interviews that teachers have not used e-modules integrated with IMTAQ values ​​and only use learning media in the form of books and videos that are in accordance with the material and results from student interviews, it was found that interest in studying biology was very high and some stated that they had already used e-modules, differing in opinion from teachers who had never used e-modules and it turned out that students only used e-modules when studying at home. . Researchers concluded from the needs analysis that teachers and students need integrated e-modules with IMTAQ values.